DIGITAL REPOSITORIES: MANAGING, STORING AND DISSEMINATING DIGITAL CONTENT (LIS TODAY, 2023)
Digital repositories have become indispensable platforms for managing, storing, and  disseminating digital content in our increasingly digitized world. These repositories serve as  virtual archives, ensuring long-term access to a wide range of digital materials, including  scholarly articles, research data, audiovisual media, and more. This article provides an  overview of digital repositories, their definition, purpose, and various types. It explores the  historical background of their development, driven by the need to preserve digital information  and ensure its availability. The article also highlights the key features and components of  modern digital repositories, including storage systems, metadata frameworks, user interfaces,  and search functionalities. Preservation strategies are discussed, emphasizing the importance  of safeguarding digital content from degradation and technological changes. Challenges  related to preservation, such as file formats, data integrity, metadata consistency, and long term storage costs, are examined, along with strategies to address them. Access and  discovery in digital repositories are explored, focusing on user-friendly interfaces, advanced  search functionalities, and metadata cataloging. Legal and ethical considerations, including  intellectual property rights, privacy, and security, are discussed to ensure compliance and  build trust among users. The article concludes by highlighting future trends and innovations  in digital repositories, such as the integration of artificial intelligence, improved semantic  search capabilities, and the adoption of blockchain technology. Digital repositories play a  vital role in the development, preservation, and accessibility of digital content, and  overcoming the challenges they face will ensure their continued value as invaluable resources  for generations to come.
Keywords: Digital Repositories; Preservation; Metadata; Blockchain